Side-dependent effect in the response of valve endothelial cells to bidirectional shear stress. (15th January 2021) - Faure, Emilie; Bertrand, Eric; Gasté, Amélie; Plaindoux, Elise; Deplano, Valérie; Zaffran, Stéphane
Abstract: Endothelial cells covering the aortic and ventricular sides of the aortic valve leaflets are exposed to different stresses, in particular wall shear stress (WSS). Biomechanical stimuli actively regulate valve tissue structure and induce remodeling events leading to valve dysfunction. Endothelial to mesenchymal transformation (EndMT), for example, has been associated with aortic valve disease. The biomechanical response of cells at different sides of the leaflets has not been clearly characterized. To analyze the mechanical response of valve endothelial cells (VECs) we developed a unique fluid activation device that applies physiologically relevant pulsatile WSS. We characterized the morphology and function of adult porcine aortic VECs derived from the opposite sides of aortic valve leaflets following exposure to different pulsatile WSS. We found that elongation and orientation of cells in response to pulsatile WSS depends on their side of origin. Quantification of gene expression confirms phenotypic differences between aortic and ventricular VECs. Aortic VECs exposed to pulsatile WSS similar to that in vivo at the tip of aortic side of the valve leaflet upregulated pro-EndMT ( ACTA2, Snail, TGFβ1 ) and inflammation ( ICAM-1, VCAM-1 ) genes, whereas expression of endothelial markers like PECAM- 1 was decreased. Conversely, ventricular-VECs showed strong increase of PECAM-1 expression and no activation of pro-EndMT marker. Finally, we found that stress-induced genes are upregulated in both cell types, at higher levels in ventricular compared to aortic VECs. Application of physiological shear stress levels using a fluid activation device therefore reveals functional differences in VECs derived from opposite sides of the aortic valve leaflets. Highlights: Biomechanical stimuli actively regulate valvular cell phenotype. Original fluid activation device to apply controlled in vivo like wall shear stress. Exposure of pulsatile shear stress to valvular cells shows a side-dependent effect.